Impacts of Regional Financial Performance And Private Investment On Public Welfare In East Java - Achmad Daengs GS; Rahmawati, Annisa; Susena, Karona Cahya; Dwi Utami, Ristianawati; Maulana, Yogi Sugiarto; Yusra, Irdha; Firmansyah, Moch. Rachmandany (International Journal of Psychosocial Rehabilitation, 2020)
The objectives of this study to analyze the effects of regional financial performance and private investment on public welfare in East Java. This research employs explanatory study with a quantitative approach. The type of data applied is quantitative data sourced from secondary data. Data collection techniques is carried out by means of literature study. The data analysis technique employed Structural Equation Model (SEM) analysis with the Partial Least Square (PLS) program. The end results of this study imply that: (1) Regional Financial Performance has no significant effect on Public Welfare in East Java; (2) Private investment has a significant effect on Public Welfare in East Java.